A Mathematical Interpretation of the Balance Sheet (Book). - Sterling, Robert R.; Colantoni, Claude S. (The Accounting Review, 1971)
Abstract Reviews the book "A Mathematical Interpretation of the Balance Sheet," by Giuseppe Palomba.